The Influence of Guesthouse Programme on Learning Outcomes of Islamic Religious Education and Ethics of Class X Girls at Nur Hidayah Sukoharjo High School - Siti Siswati; Indah Nurhidayati; Izzun Khoirun Nissa (CV. Creative Tugu Pena, 2025)
This study examines the relationship between the quality of the dormitory program (wisma) and students’ learning outcomes in Islamic Religious Education (PAI BP) among female tenth-grade students at SMA IT Nur Hidayah Sukoharjo. Employing a quantitative correlational approach, the research investigates the extent to which the dormitory program contributes to students’ academic performance in religious studies. Data were collected through questionnaires and documentation, and analyzed using correlation analysis techniques. The findings show that although the dormitory program demonstrated a moderate level of implementation quality, students’ learning outcomes in PAI BP were relatively low. Furthermore, statistical analysis indicated no significant correlation between the dormitory program and students’ academic performance in PAI BP. These results suggest that while the dormitory program may provide potential benefits for student development, it does not directly influence academic outcomes in the subject studied. This study contributes to the understanding of religious boarding school programs by providing empirical evidence that dormitory initiatives, in their current form, may not significantly impact students’ academic performance in Islamic education. The findings highlight the need for program refinement and the integration of complementary academic support strategies. They also open avenues for further research on mediating factors—such as student motivation, learning environment, and teacher support—that may strengthen the effectiveness of dormitory programs in enhancing both character formation and academic achievement.